Author-reported affiliations on abstracts accepted for the Pediatric Orthopaedic Society of North America (POSNA) Annual Meeting: A retrospective review. Issue 1 (19th January 2020) - Murphy, Robert F.; Barfield, William R.; Offerle, Thomas; Osborne, Davis; Mooney, James F.
Abstract : Professional education at academic medical meetings is under increasing scrutiny. No data have been published regarding the academic or institutional affiliations of authors who submit abstracts as part of the Pediatric Orthopaedic Society of North America (POSNA) Annual Meeting. We sought to study the self-reported institutional affiliations and other factors over a 6-year period. The POSNA annual meeting programs 2011-2016 were reviewed. The number of abstracts, including those for main program podium presentations, posters, e-posters, and subspecialty day were queried. The number of authors on each submission, presenting author's reported institutional affiliation, and involvement of a study group or database were documented. Over the 5-year study period the abstract number increased (188 abstracts in 2011 and 294 in 2016, abstracts or a 56% increase). The mean number of authors listed per abstract was five (range, 4.9 to 5.4). Nineteen percent of abstracts were affiliated with three institutions: Texas Scottish Rite Hospital (103), Boston Children's Hospital (95) and Rady Children's Hospital (84). Boston Children's Hospital and Texas Scottish Rite Hospital were most frequent in the main program. These two institutions accounted for 16% to 25% of main program podium abstracts across all years. The total number of abstracts with a study group affiliation increased over the evaluated period (five abstracts in 2011, 18 abstracts in 2016, a 4.5-fold increase). The abstract number at the POSNA annual meeting has increased substantially recently. Although the average number of authors listed on the abstract remained consistent over the review period, study groups/databases were reported as an author/source more frequently. Two academic pediatric orthopaedic centers were affiliated with approximately 20% of the main program abstracts each year. Level of Evidence: Level IV.